Farmers’ perceptions and adoption of contract farming: empirical evidence from malt barley farmers in Northern Ethiopia - Dessie Sisay Ashagrie; Gizachew Damtie Nigusie (Discover Agriculture)
Abstract The aim of this study was to analyze the factors affecting the adoption of malt barely contract farming by farmers and the perceptions of farmers about such adoption in northern Ethiopia. Multistage sampling techniques were used to select 320 malt barley producer farmers. The study employed a probit model to identify factors affecting the adoption of contract farming, and Likert scales were used to summarize the perceptions of farmers about contract farming. The probit model results showed that adoption in contract farming was significantly affected by education level, access to credit, frequency of extension contact, malt barley selling price, access to market information, distance to the main road, and cooperative membership. In addition, the Likert scale test showed that a greater percentage of the adoter respondents strongly agreed that contract farming benefits to access technology and skill development (50%) and credit provided (35%) help increase the use of agricultural inputs. On the other hand, 35.5% of noncontract farmers perceived that contract framing does not improve the livelihood of farmers, and 30.6% of the respondents strongly disagreed that inputs are not delivered in a timely manner. However, 34.4% of the nonadopter respondent farmers strongly agreed that contract farming benefits contractors more than farmers do. This study suggested that the expansion of adult education, frequent extension contact with producer farmers, setting seasonal product prices, facilitating interest-free credit for member farmers, and enhancing farmer organizations at all levels were possible recommendations for increasing farmer adoption in contract farming.